Preparation method and application of humidity-sensitive material

By combining transition metal oxides with zeolite structure organic matter precursors in heat treatment, high-sensitivity heteroatom porous carbon moisture-sensitive materials are prepared, which solves the problems of low sensitivity and slow response time of humidity sensors, and achieves minimal humidity changes reliable perception and wide application.

CN119118097APending Publication Date: 2024-12-13WUYI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411154839.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing humidity sensors have problems such as low sensitivity, slow response time, limited detection range, large device size, complex structure and difficult maintenance, which limits its application expansion.

Method used

By heat treatment of transition metal oxides and organic matter precursors with zeolite structure in a heating device, heteroatomic porous carbon with ultra-high specific surface area and abundant defect vacancies were prepared as a high sensitivity moisture-sensitive material for preparing flexibility Humidity sensor.

Benefits of technology

The prepared humidity sensor has a high sensitivity of 82.39%, can reliably sense extremely small relative humidity changes of 0.5%, and has good performance in industrial manufacturing, agricultural production, freight storage and human physiological health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a humidity-sensitive material. The preparation method comprises the following steps: carrying out heat treatment on a transition metal oxide and an organic matter precursor with a zeolite structure in a heating device with an air inlet; the transition metal oxide is arranged on the side, close to the air inlet, of the heating device, and the organic matter precursor with the zeolite structure is arranged on the side, away from the air inlet, of the heating device; the transition metal oxide is not in contact with the organic matter precursor with the zeolite structure. Through heat treatment, metal ions with high thermal mobility are doped into porous carbon obtained after carbonization of an organic matter precursor with a zeolite structure, and the prepared heteroatom porous carbon has the ultrahigh specific surface area of 1400 m < 2 > / g or above. The humidity sensitivity of the prepared humidity sensor reaches up to 82.39%, and at least 0.5% of extremely small relative humidity change can be reliably sensed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic materials and sensor technology, in particular to a preparation method and application of a humidity sensitive material. Background Art

[0002] As one of the three most widely used sensors, humidity sensors are based on the principle that humidity-sensitive materials will change with the change of water vapor content in the external environment, by adsorbing or desorbing moisture in the outside air, so that the electrical properties of the sensor itself, such as resistance, capacitance or impedance, will change. By monitoring the output signal changes connected to the sensor's peripheral circuit system, the changes in humidity in the external environment can be indirectly observed. The application scope of humidity sensors has involved many aspects such as industrial manufacturing, agricultural production, freight storage, and human physiological health. Moreover, with the rapid development of the Internet of Things in recent years, humidity sensors, as its important components, have also ushered in new development opportunities.

[0003] The time required for the adsorption / desorption of water molecules by an ideal humidity-sensitive material should be kept as small as possible, and the humidity sensor should have high sensitivity. However, humidity sensors are still faced with problems such as low sensitivity, slow response time, limited detection range, large device size, complex structure, and difficult maintenance. These problems seriously limit the application expansion of humidity sensors. At present, the commonly used humidity-sensitive materials in humidity sensors are mainly polymers, porous semiconductor ceramics, and nanomaterials. Among nanomaterials, carbon nanomaterials have been popular since they were discovered until recently. As a carbon nanomaterial, it not only has the common advantages of other types of nanomaterials, but also has a large number of active sites and a high specific surface area on its surface structure. The development of humidity-sensitive materials is also rising. However, the traditional pure carbon-based materials reported so far, such as graphene, graphene oxide, redox graphene, and carbon nanotubes, have limited humidity sensitivity in nature, resulting in low sensitivity, small detectable range, limited low humidity resolution, and slow response / recovery time.

[0004] Therefore, it is imperative to prepare a moisture-sensitive material with high sensitivity, fast response and high resolution. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a humidity-sensitive material.

[0006] The present invention also proposes the application of the above preparation method in the preparation of a flexible humidity sensor.

[0007] According to an embodiment of the first aspect of the present invention, a method for preparing a moisture-sensitive material is provided, comprising the following steps: heat-treating a transition metal oxide and an organic precursor having a zeolite structure in a heating device having an air inlet;

[0008] The transition metal oxide is placed on a side of the heating device close to the air inlet, and the organic precursor with a zeolite structure is placed on a side of the heating device away from the air inlet.

[0009] The embodiments according to the first aspect of the present invention have at least the following beneficial effects:

[0010] Under heat treatment, metal ions with high thermal migration are easily captured by a large number of N vacancies and defects downstream. After cooling to room temperature, the downstream products are collected, acid-washed, washed with water until neutral, and then dried to obtain heteroatom porous carbon (humidity-sensitive material). The humidity-sensitive material of the present invention is heteroatom porous carbon, which has ultra-high specific surface area, high porosity and abundant defect vacancies, which is conducive to the capture of water molecules by porous carbon, thereby showing a strong response to water molecules in electrical properties.

[0011] The present invention dopes metal ions with high thermal mobility into porous carbon carbonized from an organic precursor with a zeolite structure by heat treatment, and the prepared heteroatom porous carbon has a carbonization rate of 1400 m 2 / g or more. The humidity sensor prepared in this way has a humidity sensitivity of up to 82.39%, and can reliably sense at least a very small relative humidity change of 0.5%.

[0012] In some embodiments of the present invention, the heat treatment further comprises cooling to room temperature, collecting downstream products, acid washing, water washing to neutrality and then drying.

[0013] In some embodiments of the present invention, the conditions for acid washing and water washing are as follows: the downstream powder material collected after drying is added to a dilute acid solution, ultrasonically dispersed, stirred for 2 to 3 hours, centrifuged, and washed with water, and the above acid washing steps are repeated; the material collected by centrifugation is then added to a dilute acid solution and heated at 60 to 90°C for 6 hours, and finally the solution is centrifuged and washed with deionized water for 4 to 6 times until neutral; finally, ethanol is added to the collected material by centrifugation, and it is placed in a vacuum drying oven at 70°C and dried for more than 12 hours, and then ground and sampled.

[0014] In some embodiments of the present invention, the preparation method of the humidity-sensitive material comprises the following steps: laying an organic precursor having a zeolite structure and a transition metal oxide powder flat on both ends of the same porcelain boat, with a spacing of 0.5 to 2 cm, to ensure that the two are not in contact; making one end of the porcelain boat with the metal oxide powder face the air inlet, so that the transition metal oxide powder is upstream of the organic precursor powder having a zeolite structure; then placing it in a tubular furnace and heat treating it in an inert gas atmosphere of 800 to 1000°C; after the product is cooled to room temperature, the downstream product is collected, ground, pickled, washed with water to neutrality, and then dried to obtain the humidity-sensitive material.

[0015] In some embodiments of the present invention, the acid used in the pickling step includes at least one of sulfuric acid and nitric acid.

[0016] In some embodiments of the present invention, the organic precursor having a zeolite structure includes at least one of ZIF-8, ZIF-67, ZIF-90, MIL-100, UiO-66 and MOF-5.

[0017] In some embodiments of the present invention, the transition metal oxide includes at least one of tungsten trioxide (WO3), molybdenum trioxide (MoO3), copper oxide (CuO), tin oxide (SnO), lanthanum tungsten oxide (LaWO3), vanadium oxide (VO2), chromium oxide (Cr2O3), copper ferrite (CuFeO2) and lithium niobate (LiNbO3).

[0018] In some embodiments of the present invention, the method for preparing heteroatom porous carbon using an organic ZIF-8 precursor having a zeolite structure and a transition metal oxide WO3 is as follows:

[0019] A1. Weigh 7-28g of analytically pure 2-methylimidazole and add it to beaker A. Then use a measuring cylinder to weigh 105-420ml of methanol and inject it into the beaker A. Then place beaker A in an ultrasonic CNC cleaning machine and perform ultrasonic vibration for 10 minutes to ensure that 2-methylimidazole is completely dissolved in methanol to obtain solution A.

[0020] A2. Weigh 2.94-11.76 g analytical pure Zn(NO3)2·6H2O into beaker B, then use a measuring cylinder to weigh 20-60 ml methanol and inject it into beaker B. Ultrasonicate for 10 minutes to ensure that Zn(NO3)2·6H2O is completely dissolved in methanol to obtain solution B.

[0021] A3. Then, the B solution is quickly poured into the A solution, mixed, stirred, allowed to stand, washed and dried to obtain a metal organic framework material ZIF-8 precursor;

[0022] A4. The organic ZIF-8 precursor with a zeolite structure and the transition metal oxide WO3 powder are spread flat on both ends of the same porcelain boat, with a spacing of 0.5 to 2 cm to ensure that the two are not in contact; one end of the porcelain boat containing the metal oxide powder is facing the air inlet to achieve the WO3 powder upstream of the ZIF-8 precursor powder; then it is placed in a tubular furnace and heat treated in an inert gas atmosphere at 800 to 1000°C; after the product is cooled to room temperature, the downstream product is collected, ground, pickled, washed with water to neutrality, and then dried to obtain W-PC porous carbon.

[0023] In some embodiments of the present invention, the heat treatment is performed under an inert gas atmosphere;

[0024] The inert gas atmosphere is argon or nitrogen;

[0025] The flow rate of the inert gas is 2-40 mL / min.

[0026] In some embodiments of the present invention, the temperature of the heat treatment is 800-1400° C., and the holding time of the heat treatment is 1-5 hours.

[0027] The migration effect of transition metals is enhanced within the above temperature range.

[0028] In some embodiments of the present invention, the heating rate of the heat treatment is 5 to 7° C. / min.

[0029] In some embodiments of the present invention, the mass ratio of the organic precursor having a zeolite structure to the transition metal oxide is 1:0.1-10.

[0030] In some embodiments of the present invention, the tiling area is 0.5×0.5 to 4×4 cm 2 .

[0031] The paving area refers to the area occupied by the powder after it is spread.

[0032] According to an embodiment of the second aspect of the present invention, an application of a preparation method in preparing a flexible humidity sensor is proposed.

[0033] In some embodiments of the present invention, the flexible humidity sensor comprises: a flexible substrate, on which interdigital electrodes are arranged, and the humidity-sensitive material is coated on the interdigital electrodes.

[0034] In some embodiments of the present invention, the interdigitated electrodes include 5 electrode pairs, each electrode is 200 μm wide, and the electrode spacing is 200 μm; and the lead-out ends of the interdigitated electrodes are provided with electrode terminals, and the electrode terminals are also connected to electrode pins.

[0035] In some embodiments of the present invention, the method for preparing the flexible humidity sensor comprises the following steps:

[0036] S1. preparing interdigitated electrodes on the flexible substrate using a conductive silver paste;

[0037] S2. Dispersing the moisture sensitive material and covering the interdigitated electrodes to form a film.

[0038] The present invention dopes metal ions with high thermal mobility into porous carbon carbonized from an organic precursor with a zeolite structure by heat treatment, and the prepared heteroatom porous carbon has a carbonization rate of 1400 m 2 / g or more. The humidity sensor prepared in this way has a humidity sensitivity of up to 82.39%, and can reliably sense at least a very small relative humidity change of 0.5%.

[0039] In some embodiments of the present invention, in step S1, the preparation method includes printing the interdigitated electrodes by screen printing or engraving the comb-shaped interdigitated electrodes on the copper-clad film substrate by using a laser engraving machine.

[0040] In some embodiments of the present invention, in step S1, the flexible substrate includes at least one of TPI, PU, ​​PVA, PP, PVOH, PI, LCP and PDMS film.

[0041] In some embodiments of the present invention, in step S2, the dispersed dispersant includes at least one of deionized water, anhydrous ethanol, aromatic hydrocarbons, aliphatic hydrocarbons, esters and ketones.

[0042] In some embodiments of the present invention, in step S2, the concentration of the dispersed liquid after dispersion is 5 to 50 mg / mL.

[0043] In some embodiments of the present invention, in step S2, the dispersing is performed under ultrasonic conditions.

[0044] In some embodiments of the present invention, in step S2, the covering method includes at least one of drop coating, spin coating or printing.

[0045] In some embodiments of the present invention, the film forming method includes drying film forming, the drying film forming temperature is 60 to 100° C., and the drying film forming time is 60 to 120 min.

[0046] In some embodiments of the present invention, the flexible humidity sensor is applied in the fields of industrial manufacturing, agricultural production, freight storage or human physiological health.

[0047] In some embodiments of the present invention, the human physiological health field includes a respiratory monitoring mask.

[0048] When the flexible humidity sensor of the present invention is used in a respiratory monitoring mask, the three respiratory states of normal, rapid and stopped can be identified according to the measured respiratory curve, which is of great significance for clinical medical monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The present invention is a flow chart for preparing the porous carbon-based humidity-sensitive material and the flexible humidity sensor;

[0050] Figure 2 This is a SEM image of the W-PC porous carbon surface prepared in the present invention;

[0051] Figure 3 TEM image of the W-PC porous carbon surface prepared in the present invention;

[0052] Figure 4 This is a Raman spectrum of the W-PC porous carbon prepared by the present invention;

[0053] Figure 5 The humidity-resistance characteristic curve of the W-PC800 humidity sensor prepared in Example 1;

[0054] Figure 6 The adsorption-desorption curve of the W-PC800 humidity sensor prepared in Example 1;

[0055] Figure 7 The humidity-resistance response / recovery time characteristic curve of the W-PC800 humidity sensor prepared in Example 1;

[0056] Figure 8 The W-PC1000 humidity sensor prepared in Example 2 repeats the cycle curve between 11% RH and 98% RH;

[0057] Fig. 9 The resolution response curve of the W-PC800 humidity sensor prepared in Example 1;

[0058] Fig.10 The dynamic response curves of the W-PC800 humidity sensor prepared in Example 1 and the commercial humidity sensor;

[0059] Fig.11 This is a schematic diagram of the static test environment and dynamic test environment of the humidity sensor;

[0060] Fig.12 The W-PC800 humidity sensor prepared in Example 1 is used in a respiratory monitoring mask to measure the respiratory curve;

[0061] Fig.13This is the response curve of the W-PC800 humidity sensor prepared in Example 1 when a finger approaches or moves away.

[0062] Fig.14 This is the pore size distribution diagram of the W-PC porous carbon prepared in Example 1. DETAILED DESCRIPTION

[0063] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0064] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0065] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0066] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0067] Example 1

[0068] This embodiment provides a method for preparing a porous carbon-based flexible humidity sensor, comprising the following steps:

[0069] A1. Weigh 14g of analytically pure 2-methylimidazole and add it to beaker A. Then use a measuring cylinder to weigh 210ml of methanol and inject it into the beaker. Then place beaker A in an ultrasonic CNC cleaning machine and perform ultrasonic vibration for 10 minutes to ensure that 2-methylimidazole is completely dissolved in methanol to obtain solution A.

[0070] A2. Weigh 5.88 g of analytically pure Zn(NO3)2·6H2O into beaker B, then use a measuring cylinder to weigh 30 ml of methanol and inject it into beaker B. Ultrasonicate for 10 minutes to ensure that Zn(NO3)2·6H2O is completely dissolved in methanol to obtain solution B.

[0071] A3. Then, the B solution is quickly poured into the A solution, mixed, stirred, allowed to stand, washed and dried to obtain a metal organic framework material ZIF-8 precursor;

[0072] A4. The metal organic framework material ZIF-8 precursor and the transition metal oxide WO3 powder are spread flat on both ends of the same porcelain boat with a spacing of 1 cm to ensure that the two are not in contact; one end of the porcelain boat containing the metal oxide powder is facing the air inlet to achieve the upstream of the WO3 powder of the ZIF-8 precursor powder; then it is placed in a tubular furnace and heat treated in an inert gas atmosphere at 800°C; after the product is cooled to room temperature, the downstream product is collected, ground, pickled, washed with water until neutral, and then dried to obtain W-PC porous carbon.

[0073] The mass ratio of the ZIF-8 to WO3 powder is 1:1; the surface area of ​​the ZIF-8 and WO3 powders is 2×2 cm 2 ; The inert gas atmosphere is argon, the gas flow rate is 20mL / min, the heating rate is 5℃ / min, and the heat treatment holding time is 2h; the pickling and water washing conditions are as follows: the powder material after the thermal migration reaction is added to 100mL of 0.5mol / L H2SO4 solution, after ultrasonic dispersion in an ultrasonic cleaner, the solution is placed on a constant temperature magnetic stirrer and stirred at room temperature for 2h, then centrifuged using a centrifuge, and washed once with deionized water, then the above pickling steps are repeated, and the material collected by centrifugation is added to 100mL of 0.5mol / L H2SO4 solution, and placed in an 80℃ water bath and heated for 6h, and finally the solution is centrifuged and washed 4 times with deionized water until neutral to obtain heteroatom porous carbon;

[0074] A5. A dispersant is added to the heteroatom porous carbon, and a uniform dispersion is formed under ultrasonic conditions, wherein the dispersion has a liquid concentration of 5 mg / mL;

[0075] A6. Cut out 1cm 2 A TPI copper-clad film is prepared, wherein the TPI thickness is 100 μm and the copper layer is 35 μm; then a laser engraving machine is used to engrave 4 mm × 5 mm comb-shaped interdigital electrodes on the TPI film;

[0076] A7. Apply 10μL of the dispersion onto the interdigital electrodes; apply 2μL each time, and apply 5 times in total to ensure uniform coverage. Then anneal at 80℃ for 60min to obtain a humidity sensor device with a W-PC porous carbon loading of 0.1mg, denoted as W-PC800. Finally, solder two gold-plated copper needles with tin to facilitate the wiring test of the two electrodes.

[0077] The preparation process of porous carbon-based humidity sensitive materials and flexible humidity sensors is shown in the figure Figure 1 shown.

[0078] from Fig.14 It can be seen that most of the pore sizes are below 2 nm, so W-PC porous carbon has a microporous structure and high porosity.

[0079] Example 2

[0080] The present embodiment provides a method for preparing a porous carbon-based flexible humidity sensor. The metal organic framework material ZIF-8 precursor and the transition metal oxide WO3 powder in the present embodiment are heat treated in a nitrogen / argon atmosphere at 1000°C, and a humidity sensor with a loading capacity of 0.1 mg is obtained according to the method of Example 1, which is recorded as W-PC1000.

[0081] Example 3

[0082] This embodiment provides a method for preparing a porous carbon-based flexible humidity sensor, in which a metal organic framework material ZIF-8 precursor and a transition metal oxide WO3 powder are heat treated in a nitrogen / argon atmosphere at 1400°C, and a humidity sensor with a loading capacity of 0.1 mg is obtained according to the method of Example 1, which is recorded as W-PC1400.

[0083] Example 4

[0084] This embodiment provides a method for preparing a porous carbon-based flexible humidity sensor. The difference between this embodiment and Example 1 is that the mass ratio of ZIF-8 to WO3 powder is 1:0.1, and the other conditions are the same.

[0085] Example 5

[0086] This embodiment provides a method for preparing a porous carbon-based flexible humidity sensor. The difference between this embodiment and Example 1 is that the mass ratio of ZIF-8 to WO3 powder is 1:10, and the other conditions are the same.

[0087] Example 6

[0088] This embodiment provides a method for preparing a porous carbon-based flexible humidity sensor. The difference between this embodiment and Example 1 is that the organic precursor with a zeolite structure is MOF-5, the transition metal oxide is copper oxide, and the other conditions are the same.

[0089] Comparative Example 1

[0090] This comparative example provides a method for preparing a porous carbon-based flexible humidity sensor. The difference between this comparative example and Example 1 is that a transition metal oxide is in contact with an organic precursor having a zeolite structure.

[0091] The specific surface area of ​​the humidity sensitive material in Comparative Example 1 is reduced, and the humidity sensitivity of the humidity sensor prepared thereby is reduced.

[0092] Test Case

[0093] Figure 2 The SEM image of W-PC porous carbon prepared in Example 1 of the present invention ( Figure 2 (a) and Figure 2 (b) in the figure are SEM images of the same sample. Figure 2 (a) is taken at low magnification. Figure 2 (b) is a high-magnification shot). It can be seen from the figure that the surface of W-PC porous carbon is wrinkled, which makes the material have an ultra-high specific surface area.

[0094] Figure 3 This is the TEM image of the W-PC porous carbon prepared in Example 1 of the present invention. It can be seen from the figure that a large number of foam-like micropores are visible on the surface of the W-PC porous carbon, which is attributed to the thermal migration of tungsten trioxide at high temperature and the volatilization of nitrogen-containing groups and zinc in ZIF-8 at high temperature.

[0095] Figure 4 The Raman spectra of the W-PC porous carbon prepared in Example 1 and Example 2 of the present invention are shown in Figure 1 at 1350 cm -1 The D band of W-PC is not present in the original graphite due to crystal symmetry. The signal intensity indicates the degree of destruction of the W-PC lattice and the influence of the edge structure. -1 The G band represents the C atom sp 2 Hybrid internal stretching vibration, the signal intensity represents the degree of W-PC lattice arrangement. The intensity ratio of the two characteristic bands of W-PC800 and W-PC1000 is D / I G They are 1.37 and 1.22 respectively, which represent the defect density of these two samples.

[0096] Figure 5This is the humidity-resistance characteristic curve of the W-PC800 humidity sensor prepared in Example 1. It can be seen from the figure that the resistance value of the W-PC800 humidity sensor decreases with the increase of relative humidity in the relative humidity range of 11%-98%, and it shows good repeatability and stability of the resistance baseline under low humidity. According to the sensitivity formula The sensitivity was 82.39%. Fig.10 After calculation, it can be concluded that the sensitivity of W-PC1000 is 37.2%.

[0097] Figure 6 The adsorption and desorption curves of the W-PC800 humidity sensor prepared in Example 1 at various humidity levels are shown in the figure. As can be seen from the figure, the adsorption and desorption curves of the humidity sensor have a good overlap, and the maximum hysteresis value measured at 57% RH is only 1.4%.

[0098] Figure 7 This is the humidity-resistance response / recovery time characteristic curve of the W-PC800 humidity sensor prepared in Example 1. According to calculation, the response time is 22s and the recovery time is 82s.

[0099] Figure 8 The W-PC1000 humidity sensor prepared in Example 2 has a repeated cycle curve between 11% RH and 98% RH. Due to its high heat treatment temperature and low impurity content in the material, it exhibits a low basic resistance.

[0100] Fig. 9 The dynamic response curve of the W-PC800 humidity sensor prepared in Example 1 and the commercial humidity sensor (Rozonik) at the same humidity. It can be seen from the figure that in the range of 0.3%RH-90%RH, the response change of the W-PC800 humidity sensor can be almost consistent with that of the commercial humidity sensor.

[0101] Fig.10 This is the resolution characteristic curve of the W-PC800 humidity sensor prepared in Example 1. As can be seen from the figure, the response recognition of the minimum humidity change of 0.5% RH can be performed within the range of 4% RH-10% RH.

[0102] Fig.11The schematic diagram of the test environment of the humidity sensor of Example 1. The static test system includes a source meter, a wire, a humidity sensor, and a saturated salt solution with a stable humidity atmosphere. The source meter is responsible for collecting data on the resistance signal caused by the humidity signal; the wire serves to connect the source meter and the humidity sensor; the saturated salt solution is prepared into saturated solutions from eight kinds of salts, namely LiCl, CH3COOK, MgCl2, K2CO3, NaBr, NaCl, KCl, and K2SO4, and stored in a closed wide-mouth bottle to form an environment with a stable humidity atmosphere. The dynamic test system is a mixture of two background gases (air) of dry and wet, respectively, and is adjusted to the target humidity through a mass flow controller.

[0103] Fig.12 The W-PC800 humidity sensor prepared in Example 1 is applied to a respiratory monitoring mask to measure the respiratory curve, which can identify the three respiratory states of normal, rapid and stopped, and is of great significance for clinical medical monitoring.

[0104] Fingers are moist, and as they move closer to or further away from the humidity sensor, they change the humidity around the device. Fig.13 The response curve of the W-PC800 humidity sensor prepared in Example 1 when a finger approaches or moves away can be used in some non-contact applications to achieve aseptic operation in specific places.

[0105] The above embodiments and descriptions are only for illustrating the principles and best embodiments of the present invention. Without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements, all of which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a humidity-sensitive material, It is characterized in that The method comprises the following steps: heat treating a transition metal oxide and an organic precursor having a zeolite structure in a heating device having an air inlet; The heating device is provided with an air inlet, the transition metal oxide is placed on a side of the heating device close to the air inlet, and the organic precursor having a zeolite structure is placed on a side of the heating device away from the air inlet; The transition metal oxide and the organic precursor having a zeolite structure are not in contact with each other.

2. The method for preparing the humidity sensitive material according to claim 1, It is characterized in that The organic precursor with zeolite structure includes at least one of ZIF-8, ZIF-67, ZIF-90, MIL-100, UiO-66 and MOF-5.

3. The method for preparing the humidity sensitive material according to claim 1, It is characterized in that The transition metal oxide includes at least one of tungsten trioxide, molybdenum trioxide, copper oxide, tin oxide, lanthanum tungsten oxide, vanadium oxide, chromium oxide, copper ferrite and lithium niobate.

4. The method for preparing the humidity sensitive material according to claim 1, It is characterized in that The heat treatment is carried out under an inert gas atmosphere; The inert gas atmosphere is argon or nitrogen; The flow rate of the inert gas is 2-40 mL / min.

5. The method for preparing the humidity sensitive material according to claim 1, It is characterized in that The temperature of the heat treatment is 800-1400° C., and the insulation time of the heat treatment is 1-5 hours.

6. The method for preparing the humidity sensitive material according to claim 1, It is characterized in that The mass ratio of the organic precursor with zeolite structure to the transition metal oxide is 1:0.1-10.

7. Use of the preparation method according to any one of claims 1 to 6 in preparing a flexible humidity sensor.

8. The use according to claim 7, It is characterized in that The flexible humidity sensor comprises: a flexible substrate, on which interdigital electrodes are arranged, and the humidity-sensitive material is coated on the interdigital electrodes.

9. The use according to claim 7, It is characterized in that The method for preparing the flexible humidity sensor comprises the following steps: S1. preparing interdigitated electrodes on the flexible substrate using a conductive silver paste; S2. Dispersing the moisture sensitive material and covering the interdigitated electrodes to form a film.

10. The use according to claim 7, It is characterized in that The flexible humidity sensor is applied in the fields of industrial manufacturing, agricultural production, freight storage or human physiological health.

Citation Information

Patent Citations

  • Metal and nitrogen co-doped carbon-based monatomic catalyst and preparation method thereof

    CN115672375A

  • Flexible humidity sensor based on functionalized porous carbon and preparation method thereof

    CN117665053A